Identifikasi bakteri gram negatif batang pada urine suspek infeksi saluran kemih mahasiswi di Poltekkes Kemenkes Aceh - Erlinawati Erlinawati; Asri Jumadewi; Fitriana Fitriana (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Urinary tract infection is a disease caused by the growth of microorganisms in the human urinary tract.  25-35% of adult women experience UTIs based on data from clinical epidemiology studies. On this campus, students are predominantly female with busy activities, so they tend to consume less drink according to the standard and often experience symptoms of UTI caused by gram-negative rod bacteria.Objectives: to determine the presence or absence and type of gram-negative rod bacteria in the urine of female students suspected of UTI in the D-III TLM Study Program.Methods: analytical observational design with cross sectional design, which was conducted at UPTD Labkes Center and Medical Device Testing in August 2023 with a sample of 20 female students' urine.  Data analysis in this study is univariate analysis to find the number and type of gram-negative rod bacteria and observe bacterial growth.Results: the identification results showed that the number of positive samples was 75% and the negative samples were 25%.  The types of bacteria are: Escherichia coli (35%), Enterobacter Sp (20%), Citrobacter disversus (5%) and Serratia rubidae (15%).  This is because most D-III TLM students have high activity, so they pay less attention to water intake or rarely drink and they also often experience anyang or difficulty urinating which is a symptom of UTI.Conclusion: In the urine of female students suspected of UTI in the D-III TLM Study Program of the Poltekkes Kemenkes Aceh there are gram-negative rod bacteria.